The interface microstructure and tensile properties of direct energy deposited TC11/Ti2AlNb dual alloy. (15th November 2016) - Zhang, Y.Z.; Liu, Y.T.; Zhao, X.H.; Tang, Y.J.
Abstract: Direct energy deposition process based on laser and powder feeding provides powerful ability in integrated manufacturing of multi-materials components. In this work, TC11/Ti2 AlNb dual alloy thin walls were prepared by direct energy deposition process. The microstructure evolution and tensile properties of the dual alloy samples perpendicular to the interface after different heat treatments were investigated. The results indicated that there were two distinct composition transition zones between these two alloys due to the dilution effect during the process. From TC11 alloy side to Ti2 AlNb alloy side, the phase evolved as: α + β → α + α2 + β/B2 + O → α2 + β/B2 + O → α2 + B2 + O. As-deposited materials presented better mechanical performance than other two counterparts both at room temperature and 650 °C elevated temperature. For all samples, the fracture positions were not located within the interface zone, indicating the good mechanical performance of the interface zone. For demonstration, a TC11/Ti2 AlNb dual alloy blisk was prepared by this process. Graphical abstract: This work provides a useful way to fabricate near-net shape dual alloy component based on direct energy deposition with laser and powder feeding. The above formed TC11/Ti2 AlNb dual alloy blisk was prepared by this process, its inner part within the dot line was from TC11 titanium alloy, while the upper half of the blades was from Ti2 AlNb alloy, thus can meet the different properties requirements at different positions. This work investigates the interface microstructure evolution and the effect of the post heat treatment on microstructure and properties of the dual alloy in detail. The results indicated that there were two distinct composition transition zones between these two alloys due to the dilution effect during the process. From TC11 alloy side to Ti2 AlNb alloy side, the phase evolved as: α + β → α + α2 + β/B2 + O → α2 + β/B2 + O → α2 + B2 + O. As-deposited materials presented better mechanical performance than other two counterparts both at room temperature and 650 °C elevated temperature.